The effect of the Inverted row strategy on learning motivation fostudents' basic football skills (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The  research has aimed at  to set a measure of learning motivation depending on  the use of the inverted row  strategy for basic skills in football for students of the first intermediate school level, within the curriculum of the Ministry of Education, where the researcher used the experimental approach. Therefore, the sample was chosen randomly for the average Shishbar Intermediate School in Al- Mahmudiyah Education Department, where the sample was divided into two experimental groups, Division (D) and Controlling Group Division (H), and the number of each group (10) students, i.e. the total total of the research sample  is consisted of (20) student.and the pre-test for the research sample was applied through the learning motivation scale prepared by the research, after which the educational program with the strategy was applied to the research sample and continued (8) Weeks and after the completion of the educational program, the post-test of the research ample was completed, and it reached significant results through the significant differences between the pre-test and the post-test in the learning motivation for the research, sample and in intermediate school favor of the post-test.Furthermore, differences were found in the post-test of the control and experimental groups in favor of the experimental group that applied the Inverted row strategy of learning motivation for basic skills in football, so the researcher recommends applying this strategy using a measure of motivation Learning that has been prepared in other stages, because oats clear impact on students' learning motivation